1997
DOI: 10.1007/bf02290758
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure of dihydrazones obtained from the dihydrazide of 1,3,4-thiadiazole-2,5-dithioglycolic acid

Abstract: Using PMR spectroscopy we have established that dihydrazones, obtained by condensation of the dihydrazide of 1,3, 4-thiadiazole-2,5-dithioglycolic acid with aldehydes, ketones, or b-dicarbonyl compounds, exist in solutions as a mixture of stereoisomeric forms due to conformational and geometric isomerism.E',Z'-conformational (rotational) isomerism as a result of hindered rotation about the N-CO amide bond and E,Zgeometric syn-, anti-isomerism relative to the N=C bond in hydrazones [1, 2] and aroylhydrazones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…Conformational isomerism of hydrazones obtained from 2,5-dimercapto-1,3,4-thiadiazole has been studied previously [12,13]. Hydrazones in solution exist as a mixture of two conformers (anti/syn), as exemplified by doubled proton resonances assigned to the CH 2 CO, =CH and NH groups in 1 H NMR spectra.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conformational isomerism of hydrazones obtained from 2,5-dimercapto-1,3,4-thiadiazole has been studied previously [12,13]. Hydrazones in solution exist as a mixture of two conformers (anti/syn), as exemplified by doubled proton resonances assigned to the CH 2 CO, =CH and NH groups in 1 H NMR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The percentages of anti -and syn -conformers are calculated from the ratio of integral intensities of these signals. It was found that syn -conformers dominate in DMSO solution [12][13][14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…E',Z'-conformational (twisting) isomerism due to hindered rotation about an N--CO amide bond and E,Zgeometric syn-and anti-isomerism relative to a C=N bond in bisacyl hydrazone derivatives of 2-mercaptoacetic acid have already been studied by us [1,2]. However, there are no data in the literature on hydrazones of or-substituted 2-mercaptoacetic acid.…”
mentioning
confidence: 93%
“…In the same year, Al-Talib et al 13 reported that the reaction of oxalic, malonic and succinic acid dihydrazide with 2,4-pentanedione gave smoothly the corresponding oxalyl-, malonyl-and succinyl-N,N'-bis(3,5-dimethyl-1H-pyrazole). It is also important to mention that aroyl and heteroaroyl spacer bispyrazoles have been synthesized employing 1,3-dicarbonyl compounds or derivatives thereof and, for example, isophthalic acid dihydrazide 14 or 1,3,4-thiadiazole-2,5-dithioglycolic acid dihydrazide, 15 respectively.…”
Section: Introductionmentioning
confidence: 99%